New record and distribution map of parmotrema rubifaciens (parmeliaceae, ascomycota) in the neotropics - Michlig, Andrea; Rodríguez, María Pía; Ferraro, Lidia Itatí (Pensoft, 2015)
Parmotrema rubifaciens is recorded in this paper for the first time for Paraguay, expanding its known geographic distribution approximately 430 km southeast from its nearest locality. The species is characterized, illustrated, and compared with most related taxa. In addition, a map of its geographic distribution in the Neotropics is presented.
Keywords: Paraguay; Agua dulce; Norstictic acid; Dry forests; Parmotrema cristiferum; P. dilatatum; P. gardneri